Jadłowstręt psychiczny jako przejaw tendencji autodestruktywnych w świetle wybranych koncepcji psychodynamicznych – w stronę promocji wiedzy wśród rodziców i opiekunów - Cichecka-Wilk, Małgorzata (Rocznik Pedagogiczny, 2020)
Anorexia nervosa, which is one of the forms of eating disorders, can be considered as a manifesta- tion of a long and very complex process of self-destruction. Although its genesis is usually associ- ated with puberty problems, it is rarely a rapid phenomenon. It should be treated rather as a kind of epilogue of one’s personal history. Malnutrition and weight control appearing in its context are in fact a manifestation of an attempt to cope with the hardships experienced by individual. Therefore, the anorexia nervosa is not just a problem of weight or eating habits, but it’s a way of manifesting the internal problem of the individual. Its form, defined by the otherwise valid canons of beauty or success, and consolidated by behaviours learned during the use of slimming diets, is revealed, however, in connection with specific personality traits. That is why the importance of people with this disorder, to a large extent, of tendencies to self-destructive behaviour, leading more or less con- sciously to self-destruction and in extreme cases to death, is emphasized. The article deals with the problem of anorexia nervosa as a manifestation of self-destructive ten- dencies and the issue of factors and mechanisms conditioning the occurrence of self-destructive behaviour from the perspective of selected psychodynamic concepts, indicating the importance of the issue for the care and educational processes.